Patient Perceptions of Barriers to Self-Management of Breast Cancer–Related Lymphedema. (December 2018) - Ostby, Pamela L.; Armer, Jane M.; Smith, Kandis; Stewart, Bob R.
Breast cancer survivors are at lifetime risk for the development of breast cancer–related lymphedema, a chronic, potentially debilitating condition that requires life-long symptom management. Suboptimal self-management rates suggest that health care providers may not be offering educative-support options that are customized to patient-perceived needs. An Institutional Review Board–approved focus group ( N = 9) and mailed surveys ( N = 15) were used to identify (a) barriers to lymphedema self-management, (b) how breast cancer survivors with lymphedema defined education and support, (c) what type of education and support they had received, and (d) what kind of education and support they wanted. Physiological, psychological, and psychosocial factors were identified as barriers to successful lymphedema self-management. One of the main barriers identified was lack of education about lymphedema treatment and risk reduction. In addition, more than half defined support as "prescriptions" and "referrals"; therefore, it is unclear whether patients were exposed to support other than medical treatment.